PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 13 MEDAN - Tuahna Sari Nasution; Putri Kemala Dewi Lubis (STKIP Subang, 2026)
The problem in this study is the low learning outcomes of students in economics. This study aims to analyze the effect of the Creative Problem-Solving learning model on student learning outcomes in economics in grade XI students at SMA Negeri 13 Medan. This research was conducted at SMA Negeri 13 Medan, located at Jl. Karya Bersama, Titi Kuning, Medan Johor District, North Sumatra. This quantitative study used a quasi-experimental research design. The population was all 431 grade XI students. The sample size was 72 students. The instruments used to collect data were essay questions. Instrument testing included validity, reliability, discrimination, and difficulty levels. Prerequisite testing included normality and homogeneity tests. Hypothesis testing used the Independent Sample T-Test using SPPS software version 27. The results of this study indicate that there is an influence of the Creative Problem Solving learning model on learning outcomes in the economics subject of class XI students of SMA Negeri 13 Medan, with the average score of the experimental class being 84.7 higher than the control class being 65.1. And the results of the t-test obtained a t-count value of 10,512> t-table 1,994 and a significance value (2-tailed) of 0.001 <0.05, so Ho is rejected and Ha is accepted.